The Influence of Effective Leadership and Organizational Culture on Productive Managerial Systems: Workload as a Moderation Test (Case Study: Educational Organization at XYZ Institute) - Erdhianto, Yoniv; Suhariadi, Fendy (RSF Conference Series: Business, Management and Social Sciences, 2024)
Competition for education at the tertiary level is very tight; this is due to various factors, including the freedom for state tertiary institutions to seek additional operational funds so that these institutions will increase the number of students, many new tertiary institutions being established in various regions and the development of knowledge groups. And interest in prospective new students. This requires a professional institutional management strategy and the right strategy to create a productive managerial system. This research aims to find indicators that strongly influence the formation of a productive managerial system from the independent variables, namely effective leadership and organizational culture, with workload as a moderating variable. The sample in this study was a population of 256 lecturers and educational staff, where the questionnaire data obtained was processed using PLS (Partial et al.). This research shows that effective leadership and organizational culture have a positive and significant influence on workload. The indicator that has the greatest contribution to the productive managerial system of effective leadership is how to achieve organizational goals effectively. An indicator of organizational culture that strongly influences the productivity of the managerial system is the support for the tasks given. Meanwhile, workload as an intervening variable can moderate well and act as a variable that strengthens the influence of effective leadership and organizational culture variables on the productive managerial system because it can minimize the work overload aspect.